Meltwater Lenses Over the Chukchi and the Beaufort Seas During Summer 2019: From In Situ to Synoptic View. Issue 12 (2nd December 2022) - Supply, Alexandre; Boutin, Jacqueline; Kolodziejczyk, Nicolas; Reverdin, Gilles; Lique, Camille; Vergely, Jean‐Luc; Perrot, Xavier
Abstract: We investigate the Chukchi and the Beaufort seas in the Arctic Ocean, where salty and warm Pacific Water flows in through the Bering Strait and interacts with the sea ice, contributing to its summer melt. Thanks to in situ measurements recorded by two saildrones deployed during summer 2019 and to refined sea ice filtering in satellite L‐band radiometric data, we demonstrate the ability of satellite sea surface salinity (SSS) observed by Soil Moisture and Ocean Salinity and Soil Moisture Active and Passive to capture SSS freshening induced by sea ice melt. We refer to these freshening events as meltwater lenses (MWL). The largest MWL observed by the saildrones during this period occupied a large part of the Chukchi shelf, with a SSS freshening reaching −5 practical salinity scale, persisting for up to 1 month. This MWL restricted the transfer of air‐sea momentum to the upper ocean, as illustrated by measured wind speed and vertical profiles of currents. With satellite‐based sea surface temperature, satellite SSS provides a monitoring of the different water masses encountered in the region during summer 2019. Using sea ice concentration and estimated Ekman transport, we analyze the spatial variability of sea surface properties after the sea ice edge retreat over the Chukchi and the Beaufort seas. The two MWL captured by the saildrones and the satellite measurements resulted from different dynamics. Over the Beaufort Sea, the MWL evolution followed the meridional sea ice retreat whereas, in the Chukchi Sea, a large persisting MWL was generated by advection and subsequent melting of a sea ice filament. Plain Language Summary: The Arctic Ocean is an area of large variations in salinity. Salinity is a main driver of ocean circulation as it determines (with seawater temperature) the seawater density. However, very little is known about salinity variations there, due to the paucity of measurements near ice and in river plumes where surface water is freshest. Here, we use surface salinity measurements from two autonomous vehicles, named saildrones, to show that satellite measurements can identify the evolution of freshwater lenses that result from sea ice melt. Over the Chukchi and the Beaufort seas, sea surface salinity exhibits large seasonal changes, partly because of the sea ice melting. In this region, water from the North Pacific Ocean enters the Arctic Ocean, resulting in large gradients of salinity and temperature. During summer 2019, the saildrones measured the surface salinity and temperature variability as the sea ice retreated northwards. By comparing these data with the measurements from satellites, we showed that satellites can detect these pools of fresh surface water in the Arctic Ocean, increasing the field of application of satellites to understand changes in conditions that determine the Arctic's role in climate change. Key Points: Saildrones and L‐band radiometers detect large sea surface salinity variability induced by sea ice over the Chukchi and the Beaufort Sea Low surface salinity due to sea ice melting decreases the vertical extent of momentum transfer, inhibiting it beyond 10 m depth Meltwater lenses may persist more than 1 month and reach a surface salinity 5 pss fresher than surrounding waters